"A bunny is a beautiful thing" or Animals as machines (!?) - Golež Kaučič, Marjetka (Traditiones (Ljubljana), 2013)
The article proceeds from the human-animal relationship as presented in selected folk songs and seeks to redefine the traditional view of animals (as some sort of animate machines). Using ecological and philosophical premises, the author seeks to demonstrate that animals belong where human beings have already ensconced themselves. In analyzing animal ballads and humorous songs, the author discovers various images and roles of animals as well as human perceptions of the animal world either as a real microcosm or merely a metaphorical one. Research thus shifts from an analysis of motifs and themes to the concrete or cultural relationship of the human towards animals in folklore. It is shown that the relationship between humans and animals in folksongs is explicitly anthropocentric and based on two types of historical views on animals: the synanthropic view, which treats animals as harmful, and the anthropophilic view, which regards animals as useful; however, because of certain ethic dimensions this often switches to ironicization, concealing the horror of certain human acts towards animals.
Keywords: ethnology; Etnologija; folk songs; folkloristics; Folkloristika; Ljudsko slovstvo; oral literature; Ljudske pesmi; Ethnopoetics; Živali; Etnomuzikologija; folk music; Ljudska glasba; slovenske ljudske pesmi; motivika